PENGARUH CELEBRITY ENDORSES, PERSEPSI HARGA, PROMOSI, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN JILBAB - Fitaloka SM; Ratna Ekasari; Donny Arif (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2018)
Business is one of the economic pillars in today's life. The current phenomenon that is attractive among women is the hijab. Store Kinara Jilbab Taman-Sidoarjo is one of the Muslim hijab shops that pay attention to conformity between product quality and price offered to consumers.Based on the results of this study variable celebrity endorses has a t value of 2.740> t table, t value of price perception 2.592> t table, t value promotion 4,338> t table, these three variables indicate that each each has a significant influence on purchasing decisions headscarves, while the value of t product quality is 1,223 <t table, this shows that the product quality variable does not have a positive influence significant effect on the purchase of headscarves at the Kinara Jilbab Taman-shop Sidoarjo.